Uji Aktivitas Ekstrak Etanol Daun Suruhan (Peperomia Pellucida L.Kunth)Terhadap Bakteri Salmonella Thypi - Faelga Sara; Mega Sara Yulianti; Rian Wahyul Ikhtiar (LPPM POLBITRADA, 2024)
Typhoid fever is adisease caused by infection with pathogenic bacteria , namely Salmonella Thypi. One plant that has antibacterial properties is the messenger plant (peperomia pellucida L. kunth). In this study the aim was to find out how influential the variations in the concentration of suruhan leaf extract (Peperomia Pellucida L. Kunth) had on the inhibition of Salmonella Thypi bacteria. This research is a true experimental research with a post test only control design. By testing the ethanol extract of suruhan leaves (Pepepromia Pellucida L. Kunth) against Salmonella Thypi bacteria using the well diffusion method. The concetrations used were 15%, 35%, 55% and 75% and using distilled water as a negative control and chloramphenicol as a positive control. The treatment was repeated 3 times. The results of the research showed that the extract of suruhan leaves (Peperomia Pellucida L. Kunth) contain flavonoids, saponins, alkaloids and tanins. Research data was analyzed statistically using the one way ANOVA test. Suruhan leaf extract (Peperomia Pellucida L. Kunth) has a significant effect of 0.000 on Salmonella Thypi bacteria. Concentrations of 15%, 35%, 55% and 75% respectively, namely 13.33 mm, 14 mm, 17 mm and 19.67 mm. Meanwhile, the average diameter of the inhibition zone for the positive control was 31.66 mm and the negative control distilled water was 0.00 mm. Therefore, it can be concluded that the antibacterial activity of suruhan leaf (Peperomia Pellucida L. Kunth) concetrations of 155, 35%, 55% and 75% is not equivalent to the positive control (chloramphenicol) inhibition zone).